Mengidentifikasi Gesture Siswa dalam Menyelesaikan Soal Matematika Siswa Kelas VII di SMP N 2 Ampek Angkek - Dina Lorenza; M. Imamuddin (Journal on Education, 2023)
Learning activities are basically communication activities because in the learning process, teachers and students are involved in the process of delivering messages, using media, and receiving messages. Gestures are spontaneous movements of the hands or body which generally occur during face-to-face conversations. The movement is a gesture to convey a message in the form of an impression in a way that words cannot. Gestures are divided into four main categories, namely (1) iconic gestures, (2) metaphoric gestures, (3) deitic gestures and (4) beat gestures. The purpose of this study was to find out what gestures were made by class VII students of SMP N 2 Ampek Angkek during the learning process. The type of research conducted is descriptive qualitative. Sampling of this study used the Proposive Sampling technique. Data collection was carried out by observation, interviews, and video. It was concluded that students used iconic gestures 30 times, deictic gestures 25 times, and metaphoric gestures 5 times when solving math problems in comparative material. The benefits of this gesture are carried out by students who explain material in solving mathematical problems, among others, to focus attention on the intended object, describe the object being thought of, focus attention on the object being discussed, and concretize the idea being thought of. The use of gestures can also make it easier for students or listeners to understand and easily understand the material being studied or the information conveyed.